Javanese Cultural Paradoxism: A Visual Semiotics Study on Wayang Purwa Characters of Satria and Raseksa Figures - Subiyantoro, Slamet; Kristiani, Kristiani; Wijaya, Yasin Surya (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
This study aims to explore the paradoxical character values on visual semiotics wayang purwa of Raseksa and Satria profiles. Satria and Raseksa figures were selected using a purposive sampling technique, through wayang Pandavas and Kuravas. The study was designed with qualitative research approach; the data were collected using the techniques of interviews, observation, and document analysis. The data were analyzed following the steps of data reduction, data display, and verification. The results of the research revealed that in wayang, the Raseksa and Satria figures represent a paradoxical representation of both the external structure and the inner structure. The outer structure is in the form of wayang purwa visual elements, which turns out to be the opposite shape from both Pandavas and Kuravas figures. The inner structure is more about the inseparable meaning and value from the outer structure. In semiotics, the visual element (outer structure) of Pandavas and Kuravas figures can be represented or interpreted based on their values and meanings (inner structure) in addition to show a conflict of meaning. The paradoxical cultural value in Javanese culture is essentially learning experienced-based humanity values manifested through puppet characters. This is exemplified by the Islamic example of the Prophet Muhammad and its mandatory and impossible natures.Ã‚Â The wayang Satria may represent the obligatory nature (good character), and wayang Raseksa represent the impossible (bad character) of humans.